Identity Negotiation and Multilingual Innovation: The Dynamics of Mixing Dialects in an Interactive Sociolinguistic Perspective - Zultiyanti, Zultiyanti; Sarmidi, Gatot (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study aims to examine the mixture of Yogyakarta-Banyumas dialects as an identity negotiation strategy in daily interactions. The study uses a descriptive-interpretive qualitative approach with data in the form of oral speech collected through listening methods, recording techniques, and notes, then analyzed through reduction, classification, contextual analysis, and interpretation. Based on the data, lexical mixing is the most dominant phenomenon (40%), characterized by the use of Banyumasan vocabulary such as nyong and sekang in the mixed structure. Pronoun variations (17%) indicate close social relationships through the use of nyong, me, and kowe. Style shifting (13%) shows the ability of speakers to change language styles according to the context. The dominance of the Banyumas dialect (17%) affirms local identity, while the Javanese-Indonesian mix (10%) reflects modern and bilingual identities. Dialect neutralization (3%) was used to improve comprehension in cross-dialect interactions. The conclusion of this study shows that dialect mixing occurs systematically and functionally, where speakers actively choose language forms to affirm identity, adjust social relations, and maintain communication effectiveness in multicultural contexts.